Seroprevalance of babesia ovis in sheep in elazi? - Dumanli, Nazir; Köro?lu, Ergün; Düzgün, Ali; Angin, Muhammet; Küçükerden, Nihal (Scientific and Technical Research Council of Turkey, 1997)
A total of 331 sheep sera from 19 different herds in Elazi? and the surroinding regions were tested for antibody against Babesia ovis using the enzyme-linked immunosorbent assay (ELISA) test. In addition, periferal blood semears from these sheep were prepared and examined for B. ovis. The ELISA test showed that 45.0% of sheep were seropositive for B. ovis infection. Infection rate was 24.3% in sheep which were 1-12 months old and 47.6% in sheep which were older than one year. The result of the microscopical examination of blood smears was negative in terms of B. ovis. Sheep, Babesia ovis. serology, ELISA.
Elazi? Yöresinde Koyunlarda Babesia ovis'in Seroprevalansi